Effects of fetuin on zona pellucida hardening, fertilization and embryo development in cattle - Landim-Alvarenga, F. C.; Boyazoglu, SEA; Carvalho, L. R.; Choi, Y. H.; Squires, E. L.; Seidel, G. E. (Elsevier B.V., 2002)
Mammalian oocytes can undergo spontaneous meiotic maturation when they are liberated from their follicles and cultured in vitro; however, the zona pellucida (ZP) becomes resistant to chymotrypsin digestion, or hardens, when spontaneous maturation occurs in serum-free medium. Schroeder et al. [Biol. Reprod. 43 (1990) 891] described that fetuin, a component of fetal calf serum (FCS), inhibits ZP hardening during oocyte maturation. The aim of this experiment was to study the effect of the presence of cumulus cells and addition of hormones to maturation media on bovine zona hardening and embryo development in medium with and without fetuin. In Experiment 1, different concentrations of fetuin were added to the maturation medium. The time necessary for digestion of 50% of the ZP (d50) was not different when oocytes were matured in presence of 10% FCS, 1 mg/ml polyvinyl alcohol (PVA), or 4, 1 and 0.25 mg/ml of fetuin; cleavage rates were also similar. However, significantly more blastocysts (P < 0.05) were formed when FCS was used compared to PVA and 0.25 mg/ml of fetuin. In Experiment 11, we examined the influence of the presence of cumulus cells and hormones during the maturation of oocytes in media with PVA, BSA, FCS and fetuin. The d50 was significantly higher (P < 0.05) when oocytes were matured in presence of cumulus cells. The cleavage rate of cumulus-intact oocytes was similar for all groups. However, when oocytes were partially stripped before maturation, the cleavage rate was significantly higher (P < 0.05) when FCS or fetuin was used. In both stripped and non-stripped groups, significantly more blastocysts (P < 0.05) were formed when oocytes were matured with FCS compared to BSA and PVA. These results indicate that zona hardening, as described for mouse and human oocytes, does not have a large effect on bovine cumulus-intact oocytes. Apparently fetuin can be used as a substitute for FCS during bovine oocyte maturation, since it leads to similar developmental rates as FCS in intact and partially stripped oocytes. (C) 2002 Published by Elsevier B.V. B.V.
Keywords: zona pellucida hardening; fetuin; oocytes; bovine